Zambrano Cedeño,Yorgen Leyton(2023)DIVERSIDAD FLORÍSTICA Y ESTRUCTURA DEL BOSQUE SECUNDARIO “JIMÉNEZ” LOCALIZADO EN EL CANTÓN SANTO DOMINGO, PROVINCIA DE SANTO DOMINGO DE LOS TSÁCHILAS.Quevedo.UTEQ.69p. - Zambrano Cedeño , Yorgen Leyton (2023)
The present research work aimed to analyze the floristic diversity and structure of the secondary forest Jimenez located in the enclosure Palmar del Bimbe, canton Santo Domingo, province of Santo Domingo of the Tsáchilas, with average altitude of 657 meters above sea level classified in a western piedmont evergreen forest. Three sampling units of 20 x 50 m covering an area of 1000 m2 each were distributed. The results obtained determined the presence of 248 individuals greater than or equal to 7 cm of DAP, which corresponded to 48 species, 43 genera and 29 families, being the Arecaceae family the most abundant and frequent with the species Socratea rostrata and Wettinia quinaria while the most dominant was Dacryodes peruviana of the family Burseraceae and the species Socratea rostrata was registered in the Importance Value Index (IVI). Forest diversity was calculated using the Shannon-Wiener index and the results show 1,45 mean diversities in Shannon-Wiener and 0,91 high diversity in Simpson. For the analysis of the horizontal and vertical structure, DAP data were considered to categorize them into diametric classes obtaining a greater number of individuals in class I, on the other hand the total height itself that was divided by stratum (lower, middle, and upper) registering the middle stratum with the largest number of individuals.